MANAJEMEN REKRUTMEN PENGEMBANGAN SISTEM MANAJEMEN BERBASIS WEB MENGGUNAKAN ALGORITMA BIPARTITE MATCHING - Roelly Humdiana, S.Kom., MM., M.Kom; Hanes Riady (Jurnal Informatika dan Bisnis, 2013)
Information and communication technologies are used in various fields including in the recruitment process. Difficulities encountered in the field of recruitment are the job seeker must be able to find a suitable job and the employer must hire new employees at a suitable position. In addition, before job applicants are recruited, there is usually a process of selection. Most of job applicants prepare for this test by practicing answering question from the books so the test problems limited to the matter contained in the book.